RANCANG MEDIA PAS.AR BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI : PAS.AR MEDIA DESIGN BASED ON AUGMENTED REALITY TO IMPROVE COMMUNICATION SKILLS - Selindawati; Hayu, Wiworo; Gugun Gunadi (Jurnal Penjaminan Mutu, 2024)
The use of learning media in science and science subjects has a significant influence on the way students learn and understand the material. The problem that arises in the learning process at SDN Banjarsari 01 is that students currently do not receive interactive and communicative learning media in the learning process, especially in science subjects, so that students have not mastered their communication skills optimally because they are limited in understanding the material presented. This research aims to develop Augmented Reality-based PAS.AR learning media for science subjects in class V at SDN Banjarsari 01. The method used in this research is the research and development method with the ADDIE development model. In developing PAS.AR media, several stages were carried out including analysis, design, development, implementation and evaluation. Through the development of PAS.AR media based on Augmented Reality, learning becomes more interactive and communicative, so that students are able to understand the material presented by the teacher and are able to improve students' communication skills.